Long-term exposure of the Mediterranean mussels, Mytilus galloprovincialis to polyethylene terephthalate microfibers: Implication for reproductive and neurotoxic effects. (July 2022) - Choi, Jin Soo; Kim, Kanghee; Park, Kyungil; Park, June-Woo
Abstract: As one of major types of microplastics (MPs), microfibers (MFs) are widely found in the marine ecosystem and can induce diverse impacts on various marine organisms. Sedentary species, such as mussels, can act as bioindicators for monitoring marine contamination. Hence, in this study, we used mussels ( Mytilus galloprovincialis ) to examine the toxicity of polyethylene terephthalate (PET) MFs of 100 μm size at concentrations of 0.0005, 0.1, 1, 10, and 100 mg/L for 32 days. PET MFs accumulated only in the stomachs and intestines of the mussels and caused digestive tubule atrophy. After exposure to PET MFs, no alteration in the mortality rate, shell height, length, and weight of the mussels was observed. However, the gonadal index decreased with increasing concentrations of PET MFs. This is because PET MFs decrease the sex hormones estradiol and testosterone in mussels, even at environmentally relevant concentrations. Furthermore, chronic exposure to PET MFs increased the activities of antioxidant-related (catalase and superoxide dismutase) and neurotoxicity-related (acetylcholine esterase) enzymes in the digestive gland and gill tissues of mussels. In addition, cellular immune parameters of apoptosis and DNA damage were observed in mussel hemocytes. Thus, this study demonstrates the risks of MPs in real marine environments by assessing how long-term exposure to low concentrations of PET MFs can cause potential sublethal impacts and reproductive failure in mussels. Graphical abstract: Image 1 Highlights: Toxicity of PET microfibers (PET MFs) examined in Mytilus galloprovincialis mussels after 32-days exposure. PET MFs accumulated in the digestive system, causing digestive tubule atrophy. PET MFs decreased sex hormones and gonadal index in mussels. Long-term exposure of PET MFs increased activities of superoxide dismutase, catalase and acetylcholinesterase.